2004
DOI: 10.1021/ja049836i
|View full text |Cite
|
Sign up to set email alerts
|

Contingency and Serendipity in the Reactions of Fischer Carbene Complexes with Conjugated Triynes

Abstract: The first examples of reactions of Fischer carbene complexes with triynes are reported. The regioselectivity of the reaction of the two different alkyne functions in the symmetrical triyne depends on the nature of the substituent of the triyne. Bis-silyl-substituted triynes react at the central alkyne unit, whereas bis-aryl- and bis-alkyl-substituted triynes react at the end alkyne unit. The reaction of a Fischer carbene complex with a phenyl substituent also reacts with a bis-silyl-substituted triyne at the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 18 publications
2
33
0
1
Order By: Relevance
“…Our synthetic approach was different (Scheme 1): iodoalkyne 2 was synthesized by allowing alkyne 1 to react with N-iodosuccinimide (NIS) in the presence of 10 mol % AgNO 3 . [52] Elemental analysis of the resulting pale-yellow solid gave unsatisfactory results. Furthermore, energy-dispersive spectroscopy (EDS) measurements showed that large amounts of silver were present in the solid, presumably coordinated to the imidazole ring of 2.…”
Section: Resultsmentioning
confidence: 99%
“…Our synthetic approach was different (Scheme 1): iodoalkyne 2 was synthesized by allowing alkyne 1 to react with N-iodosuccinimide (NIS) in the presence of 10 mol % AgNO 3 . [52] Elemental analysis of the resulting pale-yellow solid gave unsatisfactory results. Furthermore, energy-dispersive spectroscopy (EDS) measurements showed that large amounts of silver were present in the solid, presumably coordinated to the imidazole ring of 2.…”
Section: Resultsmentioning
confidence: 99%
“…We started our investigations by examining the cyclizationalkynylation of diester 5a with triisopropylsilylethynyl bromide (4a) 9 using the conditions developed previously for oxyalkynylation (Pd2(dba)3 with DPE-Phos as ligand, Table 1). Gratifyingly, the desired carboalkynylation product was obtained in 44% yield (entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…The solid was taken up in DCM and passed through a cotton wool plug, ether was again added to precipitate out the product. After washing with more ether the crude product was dried in (9) …”
Section: [Pd(allyl)(cod)]bf4 (13)mentioning
confidence: 99%
“…To expand the substrate scope we studied this indolization procedure with new substrates like 1-bromo-2-phenylacetylene 39 and p-tosylacetylene. Three nitrosoarenes with different electronic properties, 4-nitronitrosobenzene, nitrosobenzene and 4-methoxynitrosobenzene, were selected for reaction with 1-bromo-2-phenylacetylene.…”
Section: Scheme 6 Reaction Between O-carbomethoxy-nitrosobenzene Andmentioning
confidence: 99%